Comparative Study of Microscopy and Polymerase Chain Reaction for the Diagnosis of Suspected Visceral Leishmaniasis Patients in Nepal - Pandey, K; Mallik, AK; Pyakurel, S; Pun, SB; Pandey, BD (Kathmandu University Medical Journal, 2014)
Background Visceral leishmaniasis is potentially fatal protozoan diseases caused by Leishmania donovani. Nepal is an endemic region in which visceral leishmaniasis causes a major public health problem in the lowland areas that border the endemic areas of Bihar state in India. Accurate diagnosis to inform treatment is a first step in achieving the goal of visceral leishmaniasis elimination from South East Asian regions by 2020. Objective The objective of the present study was to compare between the Microcopy and polymerase chain reaction for diagnosis of visceral leishmaniasis. Methods In the present study, 236 bone marrow aspirations were collected from suspected visceral leishmaniasis patients in Janakpur Zonal Hospital, Dhanusa district, Terai region of Nepal in between 2003-2007. We evaluated bone marrow samples by microscopic examination with subsequent testing of the same sample by polymerase chain reaction and sequence analysis. Results Giemsa’s solution stained bone marrow slides stored for over five years were used for polymerase chain reaction amplification. The result showed that 71% were polymerase chain reaction positive and 56% were microscopic positive. Out of 104 microscopic negative bone marrow samples, 15% of samples were positive by polymerase chain reaction. Conclusion Polymerase chain reaction could make a very good option for diagnosis by using less or non-invasive material from visceral leishmaniasis patients in endemic areas of Nepal. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11016 Kathmandu University Medical Journal Vol.11(1) 2013: 14-17